Indian families : contemporary family structures and dynamics - Chandra, Vinod; Blair, Sampson Lee (Contemporary perspectives on family research, 2024)
India has an intricate cultural history that extends over thousands of years. Over the past century, however, increasing modernization, along with its associated demographic shifts, has led to substantial changes in its family structures and norms. Coupled with tremendous variations across regions, ethnic groups, and religions, Indian families are complex, unique, and ever adapting. Establishing a more thorough understanding of these changes and complexities, this volume of Contemporary Perspectives in Family Research stretches across disciplines to feature a wide array of topics, including changing forms of dating and mate selection, divorce and remarriage, cohabitation, rural-urban variations in family structures, fertility aspirations, spousal relationships and marital quality, domestic violence, filial piety, inter-generational relations, and parent-child relationships. Demonstrating the tremendous diversity of families in India, as well as their ongoing evolution, Indian Families answers a clear call to dive deeper into the intimacy of the domestic sphere in one of the world's largest and fastest growing societies.